Test Of Nutrients Content Of Nitrogen, Phosphorus, And Kalium On Paddy Fields Area Of Mopuya Village Of North Dumoga Sub District Of Bolaang Mongondow Regency - Kowaas, Freandy; Karamoy, Theffie; Kumolontang, Wiesje; Luntungan, Jooudie; Kaunang, Djoni; Rondonuwu, Jenny; Kawulusan, Rafli (PPLH-SDA, Lembaga Penelitian Unsrat Manado, 2022)
Dumoga, one of some regions of Bolaang Mongondow Regency, is a central region of rice production and so has the most important role in fulfilling the effort of people’s food needs. The research aimed to know the content of nutrients of Nitrogen, Phosphorus, and Kalium in the paddy fields area of Mopuya Village of North Dumoga Sub-district of Bolaang Mongondow Regency. Analysis of soil samples in the field used Paddy Fields Test Tool (PFTT). The research was conducted for six months from March 2022 to September 2022. The method was Survey Method by sampling soil technique in compositing the samples (whether systematically, or randomized), in which the soil samples were taken on three kinds of soil conditions, i.e.: soil ready to cultivate, the soil one month after planting, and soil after harvesting. Results showed the analysis of N content of soil ready to cultivate, soil one month after planting, and soil after harvesting were low to medium (0.16% – 0.23%). The content of P-available in the soil of ready to cultivate, soil one month after planting, and soil after harvesting were very low to low (8 – 15 ppm). The content of K-available in the soil ready to cultivate, the soil one month after planting, and the soil after harvesting were low to medium (26 – 40 ppm). Keywords: Nitrogen, Phosphorus, Kalium, Paddy fields area